2018
DOI: 10.1039/c8ta06757k
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the charge storage mechanism of conductive polymers as hybrid battery-capacitor materials in ionic liquids by in situ atomic force microscopy and electrochemical quartz crystal microbalance studies

Abstract: Morphological changes of a conductive polymer in an ionic liquid during charging and discharging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The change of the material state in the redox reactions often induces a mechanical breathing strain and a dynamic change of the mechanical properties of the polymers, although there is little consensus in existing studies on how the mechanical behavior quantitatively evolves over electrochromic processes. Previous measurements of the mechanical properties of poly(3,4-ethylenedioxythiophene) (PEDOT) using acoustic impedance showed that the shear modulus was sensitive to the doping level [28][29][30] , temperature 28,29 , electrolyte 28,29 , crosslinker 31,32 , and even film thickness 33 . Ispas et al 28 .…”
mentioning
confidence: 99%
“…The change of the material state in the redox reactions often induces a mechanical breathing strain and a dynamic change of the mechanical properties of the polymers, although there is little consensus in existing studies on how the mechanical behavior quantitatively evolves over electrochromic processes. Previous measurements of the mechanical properties of poly(3,4-ethylenedioxythiophene) (PEDOT) using acoustic impedance showed that the shear modulus was sensitive to the doping level [28][29][30] , temperature 28,29 , electrolyte 28,29 , crosslinker 31,32 , and even film thickness 33 . Ispas et al 28 .…”
mentioning
confidence: 99%
“…The charge storage of conducting polymers occurs not only on the surface (or near surface) but also throughout the entire bulk of materials, displaying both pseudocapacitive and battery-type behaviors. [129,130] Research on conducting polymers toward Si electrodes has extensively focused on the synergistic effect of Faradaic charge transfer in conducting polymers and double layer capacitance based on large surface area of Si nanostructures. Following a CVD route, Aradilla et al synthesized Si nanowires based on VLS mechanism via gold catalysis, and then coated with PEDOT by electrochemical polymerization.…”
Section: Conducting Polymers For Si Electrodesmentioning
confidence: 99%
“…A recent in situ atomic force microscopy study revealed the hybrid battery-pseudocapacitive behavior of conducting polymers in ionic liquids, where the conducting polymers demonstrate pseudocapacitive behavior at a high charging condition, and a battery-type behavior at a low charging condition. [129] Furthermore, studies on thin-film electrochemistry of conducting polymers show that as the film thickness increases, the pseudoca-pacitive characteristic changes to battery-type due to the mass transport restriction within the polymer film. [130] Conducting polymers such as polypyrrole (PPy), polyaniline (PANI), polyacetylene (PA), and poly(3,4-ethy lenedioxythiophene) (PEDOT) have been widely investigated as electrode materials of supercapacitors.…”
mentioning
confidence: 99%
“…Since their discovery in 1977 and subsequent Nobel Prize in 2000, conducting polymers (CPs) have been a breakthrough in material science with a wide range of applications in electronics (e.g., ChemFET, flexible circuits, OLED), [1][2][3] solar cell technology, [4][5][6][7][8] batteries (e.g., supercapacitors) [9][10][11][12][13] and biomedical engineering (e.g., electrode coating for recording and stimulation, drug delivery, scaffolds for tissue engineering). [14][15][16][17][18][19][20] These materials are highly versatile thanks to their chemical structure consisting of repeating alternating chains of single and double (π-π) carbon bonds, allowing electrons to move freely alongside the polymeric chains.…”
Section: Introductionmentioning
confidence: 99%